DESAIN KOMUNIKASI VISUAL SEBAGAI MEDIA INFORMASI PADA DITJEN APTIKA KEMENTERIAN KOMUNIKASI DAN INFORMATIKA JAKARTA - Po. Abas Sunarya; Lisa Anisah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2018)
Amid the millenial generation of rigorous and technologically advanced, every creative person is required to have high competitiveness and personal qualities both personal and expertise so as to be able to compete in the real world of work. Not only that, the company is also required to have adequate technology and personal quality in order to compete in this era of globalization. Therefore created a project that makes one of the programs to gain experience more apply and practice into a real work. This project produces design in the form of visual communication such as flyer, brochure, book cover, and logo that become important information related and applied to the Ministry of Communication and Information Jakarta. This research is also expected to present a communication that has an informative, entertaining, educative and framed visualization in planning and supervision under the applicable law payments.